2021
DOI: 10.1093/heapol/czab096
|View full text |Cite
|
Sign up to set email alerts
|

Big data analytics and COVID-19: investigating the relationship between government policies and cases in Poland, Turkey and South Korea

Abstract: We used big data analytics for exploring the relationship between government response policies, human mobility trends and numbers of coronavirus disease 2019 (COVID-19) cases comparatively in Poland, Turkey and South Korea. We collected daily mobility data of retail and recreation, grocery and pharmacy, parks, transit stations, workplaces, and residential areas. For quantifying the actions taken by governments and making a fairness comparison between these countries, we used stringency index values measured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…From these findings, it is concluded that the restrictions and prohibitions imposed by the government in coping with COVID-19 have had significant impacts on the management of ED operations. This result is in line with the existing studies (Akter & Wamba, 2019 ; Haldane & Morgan, 2021 ; Sözen et al, 2022 ). Our findings contribute to the literature by investigating the effects of system dynamics-related and government-imposed actions together and comparatively for different operations of EDs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…From these findings, it is concluded that the restrictions and prohibitions imposed by the government in coping with COVID-19 have had significant impacts on the management of ED operations. This result is in line with the existing studies (Akter & Wamba, 2019 ; Haldane & Morgan, 2021 ; Sözen et al, 2022 ). Our findings contribute to the literature by investigating the effects of system dynamics-related and government-imposed actions together and comparatively for different operations of EDs.…”
Section: Discussionsupporting
confidence: 93%
“…However, we aimed to identify the impacts of policy-based factors on ED operations by adopting our model into a case study representing the overcrowding of ED environments and frequently unnecessary ED visits. This result supports the existing studies reporting decreased patient volumes due to the governmental actions taken in fighting COVID-19 (Kendzerska et al, 2021 ; Sözen et al, 2022 ). It also enhances literature by considering this effect in developing prediction models for patient volumes, average stay lengths of patients, and resource utilization of EDs during this pandemic period.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This raises the question of whether these fiscal measures can be used as useful indicators of the spread of COVID-19. The most commonly used statistics in the literature are either unstandardized or standardized measures of COVID-19 cases and deaths, whereby unstandardized variables are placed on the same scale to allow comparisons ( Sözen, Sarıyer & Ataman, 2022 ). Another critical statistic for measuring a country's success in fighting the pandemic is the case-fatality ratio, defined as the ratio of COVID-19-related deaths to confirmed COVID-19 cases (Ivanda et al, 2021; Spychalski, Błażyńska-Spychalska & Kobiela, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 In fighting against the pandemic, there exist tremendous worldwide efforts to keep the spread of the virus under control and protect the functioning of health systems. 2,3 Mask-wearing and stay-at-home campaigns and obligations, travel bans, school and work closures, entertainment place closures, and so on, are just a few of the policies taken by governments in managing the pandemic environment.…”
mentioning
confidence: 99%